2017
DOI: 10.1137/16m1067408
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Airy Operator on the Line with a Semipermeable Barrier

Abstract: Abstract. We consider a suitable extension of the complex Airy operator, −d 2 /dx 2 + ix, on the 4 real line with a transmission boundary condition at the origin. We provide a rigorous definition of 5 this operator and study its spectral properties. In particular, we show that the spectrum is discrete, 6 the space generated by the generalized eigenfunctions is dense in L 2 (completeness), and we analyze 7 the decay of the associated semi-group. We also present explicit formulas for the integral kernel of 8 the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(83 citation statements)
references
References 26 publications
(52 reference statements)
2
81
0
Order By: Relevance
“…In the former papers, the effect of diffusive exchange between compartments onto the MR signal was investigated (see also [18] for a recent overview and references on this topic). In turn, a general asymptotic construction presented in [17] extends and improves the earlier result by de Swiet and Sen for bounded domains. It was shown that, for large enough g, the eigenfunctions of the BT-operator are localized near the boundary points r j at which the normal vector to the boundary is parallel to the gradient direction.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In the former papers, the effect of diffusive exchange between compartments onto the MR signal was investigated (see also [18] for a recent overview and references on this topic). In turn, a general asymptotic construction presented in [17] extends and improves the earlier result by de Swiet and Sen for bounded domains. It was shown that, for large enough g, the eigenfunctions of the BT-operator are localized near the boundary points r j at which the normal vector to the boundary is parallel to the gradient direction.…”
supporting
confidence: 78%
“…More recently, the analysis was extended to multiple intervals with semi-permeable boundaries [15,16] and to arbitrary planar domains [17]. In the former papers, the effect of diffusive exchange between compartments onto the MR signal was investigated (see also [18] for a recent overview and references on this topic).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this the reader may consult the work of Lions and Magenes [8], Tanabe [9], Temam [10], Amann [11]. Also recently, e.g., Almog, Grebenkov, Helffer, Henry studied variants of the complex Airy operator via such triples [12][13][14], and our results should at least extend to final value problems for those of their realisations that have non-empty spectrum. To compare (6) with the analogous Cauchy problem, we recall that whenever u + Au = f is solved under the initial condition u(0) = u 0 ∈ H, for some f ∈ L 2 (0, T; V * ), there is a unique solution u in the Banach space X =L 2 (0, T; V) C([0, T]; H) H 1 (0, T; V * ),…”
Section: The Abstract Final Value Problemmentioning
confidence: 88%
“…Recently Grebenkov, Helffer and Henry [14] studied the complex Airy operator A = −∆ + i x 1 in dimension n = 1. They considered realizations defined on R + by Dirichlet, Neumann and Robin conditions using the Lax-Milgram lemma, so results on boundary homogenous final value problems for − d 2 dx 2 + i x should be straightforward to write down, as in Section 5.1.…”
Section: Remark 18mentioning
confidence: 99%